PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Survei pada Pengguna Jasa Layanan Kantor Pos Boyolali) - Retno Susanti, Yessi Agustianti, Alwi Suddin & (Universitas Slamet Riyadi, 2018)
The purpose of this study is to analyze (1) the influence of servicequality on customer satisfaction Post Office Boyolali. (2) the influence ofservice quality on customer loyalty of Post Office Boyolali. (3) the influence ofcustomer satisfaction on customer loyalty of Boyolali Post Office. (4) theinfluence of service quality on customer loyalty mediated by customersatisfaction. The research was conducted at Boyolali Post Office. Thepopulation of 432 people. Samples used as much as 20% of the totalpopulation of 130 respondents. Sampling technique with purposive sampling,and accidental sampling. Data collection techniques using questionnaires.Data analysis with path analysis model and mediation variable using SobelTest. The result of the research shows that service quality variable hassignificant influence to customer satisfaction. Quality of service has asignificant influence on customer loyalty. Customer satisfaction has asignificant influence on customer loyalty. Customer satisfaction is able tomediate the influence of service quality on customer loyalty.Keywords: Loyalty, satisfaction, service quality